Acute appendicitis in overweight patients: the role of preoperative imaging. Issue 1 (December 2016) - Sauvain, Marc-Olivier; Tschirky, Sandra; Patak, Michael; Clavien, Pierre-Alain; Hahnloser, Dieter; Muller, Markus
Abstract Background The diagnosis of acute appendicitis in overweight patients is challenging due to the limited value of the clinical examination. The benefits of ultrasonography and abdominal CT have been studied in the general population, but there is limited data regarding their use in overweight and obese patients with suspected appendicitis. This study analyzes the role of preoperative radiological modalities in overweight patients with suspected appendicitis. Methods Retrospective analysis of a prospectively acquired database including 705 patients operated for suspected acute appendicitis. Patients were divided into two groups according to their BMI (BMI ≥25 kg/m2 (n  = 242) and BMI <25 kg/m2 (n  = 463)). The use of preoperative radiological modalities, laboratory findings and outcome parameters were analyzed. Results Ultrasonography was the preferred radiological assessment in our cohort (68 % in BMI <25 kg/m and 52.4 % in BMI ≥25 kg/m2 ). However, it was non-conclusive in 42 % of overweight as compared to 6 % in patients with a BMI < 25 (p  < 0.0001). This difference was particularly obvious between female patients (8 % of non-conclusive US for BMI <25 kg/m2 vs 52 % for BMI ≥25 kg/m2, p  < 0.0001). Significantly more CT scans were performed in overweight patients (37 % vs. 20 %; p <0.0001). The accuracy of CT did not differ according to BMI (85 % vs. 88 %;p  = 0.76). Preoperative radiological imaging did not significantly delay surgery. Laparoscopy was the preferred approach for both groups (98.2 % vs 98.7 %, P  = 0.86) with an overall conversion rate of 4 %. The overall rate of negative appendectomy was 10 %. Conclusions The role of ultrasonography in patients with BMI ≥25 kg/m2 with suspected acute appendicitis is questionable due to its high rate of non-conclusive findings. Therefore, abdominal CT scans should be preferred to investigate suspected appendicitis in overweight patient if clinical findings are not conclusive.